Technique Self Management In Overcoming Procastination Of Junior High School Students - Fitrianingsih, Fitrianingsih; Sari Rahayu, Herlis Wulan; Najahah, Khoerun (Arbain Publishing, 2024)
Procrastination is Wrong One problems that occur among junior high school students or School Intermediate First (Junior High School). On method researcher This use qualitative descriptive , which will to study more in about a phenomenon that has happen in today's era And cases - cases or incident Which happen in the field . Study This aiming For describe level procrastination academic junior high school students and aiming method For overcome to be able to changed . Participants educate This is junior high school level very difficult manage time between play And Study so that cause flavor lazy For go to school on student level JUNIOR HIGH SCHOOL This . Results from interview researcher This disclose that This junior high school student experience disturbance like often Sleep in class , often using gadgets in class , and more Like play than Study.